Abdurauf Fitrat is a Talented Poet - Kamalova Dilfuza Obidovna (Genius Journals, 2022)
The article examines the poetic syntax of A. Fitrat's lyrical heritage, which left an indelible name in the Uzbek poetry of the XX century, the originality of ideas and images in terms of form, content and place in the modern literature. Also, the influence of A. Fitrat's poetry on Uzbek poetry and scientific views on the theory of literature are analyzed and some conclusions are stated.
Keywords: jadid literature; independence; nationalism; pathos